Pengembangan Media Pembelajaran E-Book Berbasis Power Point pada Mata Pelajaran Fikih Fase E dengan Materi Haji dan Umroh Kelas X di Ma An-Nafi’ah Baureno - Aliyatul Musyafaah; Ida Fauziatun Nisa’; Usman Roin (Universitas Muhammadiyah Surabaya, 2024)
Learning media is a means in the delivery of learning that is expected to be able to make students active and enthusiastic in the learning process. In some institutions in particular in the MA An-Nafi’ah that are limited in the use of learning media. Some of the students in the classroom behaved inappropriately and refused to follow the teaching because of the teachers' teaching methods. Thus, the use of power points was still limited and less innovative so that power-point-based e-books were introduced in MA An-Nafi’ah Banjaran Baureno. So the researchers undertook development to reduce student boredom. Because in the subject matter, especially with the material of Hajj and Umroh, the delivery of the material requires accurate depiction so that students can capture what is delivered by the teacher. Thus this research was carried out at the MA-An-Nafi’ah Banjaran Baureno. The research method used is the Research and Development (R&D) method with the ADDIE model covering analysis, design, develophment, implementation and evaluation. Data on this developmental research is observations, interviews, lifts, and documentation. Evaluations in powerpoint-based e-book media include media expert validation, material expert validation, large-group test, and teacher response related media power point-based E-book. The results of the power point based e-Book media development research include validation of media expert obtaining a 90% rating with a highly qualified category, 100% material expert evaluation with a very qualified Category, teacher responses obtained a 96% rating of a highly calified Category and large group trial obtains a 88.4% rating with very qualifying Categories, then stated that Powerpoint based E-Book products are highly qualifiable for use in the learning process. Keywords: Power Point Based E-Book Media, Haji and Umroh Phase E Materials, Fikih